EVALUASI PENEGAKAN DIAGNOSIS TUBERKULOSIS ANAK BERDASARKAN PETUNJUK TEKNIS TUBERKULOSIS ANAK 2016 DI RSU BMC PADANG - Resti Ayu Safitri; Finny Fitry Yani; Al Hafiz; Rinang Mariko; Rima Semiarty; Elmatris Elmatris (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Background: Tuberculosis (TB) is a contagious infectious disease that is still the main cause of health problems and one of the main causes of death in children in the world. The main problem in diagnosing TB in children is that it has not been properly socialized, understood, and implemented by most general practitioners and pediatric specialists, according to the 2016 Technical Guidelines for the Management and Management of Childhood Tuberculosis. Objective: The diagnosis of TB is mostly based on clinical considerations without making efforts to search for bacteriological confirmation, so evaluation is needed towards the implementation of the diagnosis of TB in children based on the 2016 Technical Guidelines for the Management and Management of Childhood Tuberculosis algorithm at RSU BMC Padang. Methods: This type of research is a descriptive study with a cross-sectional retrospective study design using medical record data from pediatric TB patients recorded at the children's clinic at RSU BMC Padang in 2022. The research was conducted at RSU BMC Padang for six months. The sampling technique used was total sampling with a sample size of 137 data. Results: Most patients had symptoms of chronic cough (76.6%), more than half had fever for ≥ 2 weeks (62.8%), weight loss (67.2%), and general malaise (90.5%). Only a small portion (8%) of pediatric TB patients underwent TCM examination, and the majority (89.8%) underwent chest x-rays, and generally (97.1%) underwent tuberculin. All patients were diagnosed with clinical pediatric TB. Conclusion: From the research that has been carried out, it can be concluded that almost all children's TB is diagnosed positively, without implementing the complete diagnosis algorithm in the 2016 Technical Guidelines for the Management and Management of Childhood Tuberculosis. Completeness of supporting examinations, especially TCM, must be paid attention to by the clinician so that all algorithms are fulfilled.